Rates of criminal victimization in an early intervention for psychosis service ‐ a cross sectional survey. Issue 6 (26th January 2017) - Jones, Rowena; Banbury, Luke
Abstract : Background: There is a growing body of research looking into the high rates of victimization amongst people with severe mental illness. Studies to date have tended to look at victimization rates in people with chronic mental illness over a wide age range. However, national crime surveys indicate that younger people are more likely to be the victim of crime than older people. There is also evidence that people from ethnic minorities are more likely to experience and less likely to report criminal victimization. This study therefore aimed to look at victimization rates specifically in young people with first episode psychosis (FEP) in Birmingham, one of the most youthful and ethnically diverse cities in the UK. Methods: Patients with FEP under the South Birmingham Early Intervention Service were asked to complete a modified version of the Crime Survey for England and Wales (CSEW). Data was compared to control‐group data from the CSEW 2014. Results: Patients with FEP were significantly more likely to be victims of crime, in particular violent crime, than their age‐matched counterparts. The overall victimization rate was 39%. Black and Minority Ethnic (BME) groups were more likely to be victims of personal and violent crime than the white FEP population. Victimization rates were broadly in keeping with other UK and international studies. Conclusions: Young people with FEP, particularly those from BME backgrounds, are at significantly greater risk of victimhood than the general population of the West Midlands.